Synthesis and characterization of ultra violet (UV) curing adhesive from natural oils / Ahmad Faiza Mohd - Mohd, Ahmad Faiza (Institute of Graduate Studies, UiTM, 2017)
Bio-Adhesive from natural oil is expected to become important sources of renewable raw material in the resin industry. The synthesis and modification process of abundant natural oil such as sunflower, vegetable, palm oil, jatropha oil are the strategy to study the potential of green resin in various applications. In this study, natural oil from sunflower, rapseed and vegetable oils were chosen to be synthesized and modified to new natural modified resin which could be exploited as adhesive and coatings resin. Oils had been chosen according to their unsaturation in glyceride. The starting materials are in the form of fatty acids and triglyceride to produce bioadhesive resin. Fatty acid or triglyceride had been synthesized to produced modified oil via various routes of synthesize method, consist of amide prepolymer, urethane oil prepolymer and fatty acid dimers. A stoichiometry and reaction temperature was studied to explore the kinetic of reactions in each of synthesize route. Gel permeation chromatography, wet chemistry and spectroscopy techniques; Fourier transform infrared (FTIR), Nuclear Magnetic Resonance (NMR) were used as characterization method to identify the functional group and chemical properties of prepolymers. Then, functional groups in these three prepolymers were activated using epoxidation and acrylation process. Epoxidation process was done via in-situ epoxidation by peroxoformic acid. This process had been optimized with the study of the effects of formic acid and hydrogen peroxide, temperature and solvents in different type of prepolymers…